Pengaruh Supervisi Dan Coaching Terhadap Kinerja Perawat - Syabanasyah, Inas; Solehudin, Solehudin (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Effective supervision focuses not only on supervision, but also on developing nurses' skills and knowledge. Structured coaching can also create a positive work environment, where nurses feel more involved and motivated to provide the best service to patients. This study aims to comprehensively analyze the effect of supervision and coaching on nurse performance. The type of research used is quantitative correlation analysis research with a cross-sectional approach. The population in this study were 360 ​​nurses at a private hospital in Jakarta. The sampling technique used was convenience sampling and the sample calculation formula used Slovin, so that a sample of 190 respondents was obtained. The data collection tool used a questionnaire consisting of 30 questions about supervision, coaching and performance. The statistical analysis used was multiple logistic regression. The results of the study showed that the majority of nurses (65.8%) did not receive programmed supervision. Most nurses (64.2%) reported that the coaching they received was still less than optimal. The majority of nurses (64.7%) had high performance, but there were still 35.3% who had low performance. Supervision has the greatest influence on nurse performance (p value 0.001). Coaching also has an effect, but its effect is smaller than supervision p value 0.005. The practical implication is that increasing more programmed supervision and more effective coaching can significantly improve nurse performance.